Oral health and oral-health-related quality of life in people with X-linked hypophosphatemia - Jannik Steur; Lauren Bohner; Jochen Jackowski; Marcel Hanisch; Ole Oelerich (BMC, 2024)
Abstract Background X-linked hypophosphatemia (XLH) is a type of vitamin D-resistant rickets. It is the most common form of it and is related with oral health problems. This study aimed to analyze the OHRQoL of people suffering from XLH and measure physical oral health to confirm or refute evidence of reduced oral health. Methods The German version of the Oral Health Impact Profile (OHIP-14G), was used to measure OHRQoL. All study participants underwent clinical examination, and oral health was scored using the Physical Oral Health Index (PhOX). Results A total of 26 people participated in the study, of whom five were male and 21 were female. The average participant age was 40.9 ± 12.8 years. The OHIP-14G score was 14.3 (± 12.1; 95% CI: 9.37. 19.16) points (range 0-44 points). The PhOX score was 77.1 (± 9.9; 95% CI: 73.10-81.13) points (range 61-95 points). Conclusions The results of this study confirm that oral health and OHRQoL are both reduced in the studied cohort of people affected by XLH. Particular attention should be paid to perfect oral hygiene in people with XLH, as the impaired enamel mineralisation increases the risk of caries and thus also the occurrence of apical infections.